Menanamkan Pemahaman Moderasi Beragama Melalui Aktivitas Belajar-Mengajar Di TPQ Madrasatul Qur’an Desa Kalicinta Lampung Utara - Meiliana, Evri; Anggraini, Soca; Marita, Selly (PT Ruang Publikasi, 2026)
Al-Qur'an Education Parks (TPQ) are non-formal educational institutions that play a significant role in shaping children's character and morals from an early age. However, the majority of TPQs still focus primarily on reading and memorizing the Quran, while instilling the values ​​of religious moderation has not been optimally implemented. The main challenge is how to internalize an understanding of religious moderation among students so that they can grow into a tolerant, peace-loving, and respectful generation. This community service activity aims to contribute to creating social harmony by teaching religious moderation from a young age. TPQ Madrasatul Qur'an was chosen as the target Islamic elementary education institution for this activity, with an emphasis on strengthening the values ​​of tolerance, justice, and balance. This community service activity aims to disseminate an understanding of religious moderation within the TPQ through interactive methods, including storytelling, informal discussions, good moral habits, and simple social activities. The results of this activity indicate that the students experienced an increase in their understanding of moderation, cooperation, and the habit of respecting differences. The method applied in the community service program was Participatory Action Research (PAR). In this method, ustadzah (preachers), ustadzah (male and female), and children actively participated in guidance and educational activities appropriate to their context. Data collection was carried out through observation, recording, and direct participation that occurred during religious guidance and development at the TPQ Madrasatul Qur'an. The findings obtained illustrate that learning strategies that focus on the values ​​of religious moderation are able to strengthen children's religious understanding in a fair and non-discriminatory manner. This program also succeeded in increasing understanding and love for the nation and state, in addition to a critical response to radical teachings with the principle of anti-violence committed in the name of religion. It is hoped that the habituation of these values ​​from childhood can become a strong foundation for creating a harmonious, just society with a national perspective.